Identification and functional characterization of a c-type lysozyme from Fenneropenaeus penicillatus. Issue 88 (May 2019) - Cai, Shuanghu; Zhang, Yilin; Wu, Fan; Wu, Rimin; Yang, Shiping; Li, Ya; Xu, Youhou
Abstract: Lysozyme is an important defense molecule of the innate immune system and possess high antimicrobial activities. In this study, a full-length c-type lysozyme cDNA ( Fplysc ) was cloned and characterized from Fenneropenaeus penicillatus . The cDNA contains an open reading frame of 477 bp encoding 158 amino acids, with 53–94% identity with those of other crustaceans. The recombinant Fplysc had antibacterial activities against Gram-positive bacteria (Streptococcus agalactiae and Micrococcus luteus ) and Gram-negative bacteria ( Vibrio alginolyticus and Escherichia coli ), and showed antiviral activity against WSSV and IHHNV. The qRT-PCR analysis showed that Fplysc expression levels were most abundant in hemocytes and less in eyestalk. The expression levels of Fplysc were significantly upregulated in gill, intestine and hemocytes when challenged with WSSV and V. alginolyticus . Fplysc- silencling suppressed Fplysc expression in cephalothoraxes and increased mortality caused by WSSV and V. alginolyticus, and exogenous rFplysc led to a significant decrease of shrimp mortality by injecting rFplysc into Fplysc silenced shrimp, suggesting Fplysc is the important molecule in shrimp antimicrobial and antiviral response. In conclusion, the results provide some insights into the function of Fplysc in shrimp against bacterial and viral infection. Highlights: An c-type lysozyme homolog ( Fplysc ) was cloned from F. penicillatus. The rFplysc had antibacterial activities against bacteria. Fplysc was constitutively expressed in some tissues. Fplysc expression levels were significantly up-regulated in some tissues with microbial challenge. Fplysc- siencling and exogenous rFplysc increased and decreased mortality of shrimp caused by pathogens, respectively.